2012
DOI: 10.1111/j.1365-2559.2012.04339.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasmablastic lymphoma of the elderly: a clinicopathological comparison with age‐related Epstein–Barr virus‐associated B cell lymphoproliferative disorder

Abstract: PBL-E shares some clinical features with AR-EBVLPD, such as HIV negativity, old age, and EBV infection, no known immunosuppressive condition but there are some differences such as a higher ratio of extranodal involvement and better prognosis. PBL-E is a newly recognized condition and should be distinguished from HIV-positive PBL, sharing features with AR-EBVLPD in particular, immunosenescence of the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 40 publications
3
38
0
Order By: Relevance
“…MYC rearrangement has been found in 40% to 50% of the cases with the IG as major translocation partner (83% of cases) and associated with strong protein expression. [62][63][64] These rearrangements seem to be more common in HIV-related PBL than in other subgroups of patients and are associated with a shorter overall survival. 65 Some cases of PBL with MYC rearrangements have some overlapping features with plasma cell myeloma, such as monoclonal serum immunoglobulins and lytic bone lesions.…”
Section: Myc Activation In Other Aggressive Large B-cell Lymphomamentioning
confidence: 99%
“…MYC rearrangement has been found in 40% to 50% of the cases with the IG as major translocation partner (83% of cases) and associated with strong protein expression. [62][63][64] These rearrangements seem to be more common in HIV-related PBL than in other subgroups of patients and are associated with a shorter overall survival. 65 Some cases of PBL with MYC rearrangements have some overlapping features with plasma cell myeloma, such as monoclonal serum immunoglobulins and lytic bone lesions.…”
Section: Myc Activation In Other Aggressive Large B-cell Lymphomamentioning
confidence: 99%
“…24 Using a reverse transcriptionpolymerase chain reaction method, Nguyen-Van et al 19 showed that many EBV-positive DLBCL of the elderly and EBV-positive PTLD resembling DLBCL shared features of EBV latency type III. A relatively high frequency of EBNA2 expression (28%-32%) has been observed in several studies.…”
Section: Epidemiologymentioning
confidence: 99%
“…18,42 Plasmablastic lymphoma of the elderly is another newly recognized entity with a relatively indolent clinical course and better prognosis compared with other agerelated EBV-positive B-cell LPDs. 24 Plasmablastic lymphoma of the elderly shares features with age-related EBV-positive B-cell LPDs, including older age, immunosenescence, EBV infection, HIV negativity, and an ABC immunophenotype, although contrasting features include more frequent extranodal involvement and MYC translocations and EBV type I latency pattern. 24 …”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…These tumors usually present in extranodal sites and frequently in the mucosae of the head and neck region in patients with different immunodeficiency states, mainly HIV infection. [72][73][74] MYC translocations are encountered in 41% to 49% of PBL cases, virtually all of them with an IG gene as a partner and usually in the context of multiple chromosomal aberrations, and seem to confer an inferior prognosis. [73][74][75][76] MYC activation also seems to play a role in the progression of plasma cell neoplasms, particularly from monoclonal gammopathy of undetermined significance to PCM.…”
Section: Dh/th Lymphomamentioning
confidence: 99%